Delayed Cranioplasty: Outcomes Using Frozen Autologous Bone Flaps. Issue 3 (September 2015) - Hng, Daniel; Bhaskar, Ivan; Khan, Mumtaz; Budgeon, Charley; Damodaran, Omprakash; Knuckey, Neville; Lee, Gabriel
Reconstruction of skull defects following decompressive craniectomy is associated with a high rate of complications. Implantation of autologous cryopreserved bone has been associated with infection rates of up to 33%, resulting in considerable patient morbidity. Predisposing factors for infection and other complications are poorly understood. Patients undergoing cranioplasty between 1999 and 2009 were identified from a prospectively maintained database. Records and imaging were reviewed retrospectively. Demographics, the initial craniectomy and subsequent cranioplasty surgeries, complications, and outcomes were recorded. A total of 187 patients underwent delayed cranioplasty using autologous bone flaps cryopreserved at −30°C following decompressive craniectomy. Indications for craniectomy were trauma (77.0%), stroke (16.0%), subarachnoid hemorrhage (2.67%), tumor (2.14%), and infection (2.14%). There were 64 complications overall (34.2%), the most common being infection (11.2%) and bone resorption (5.35%). After multivariate analysis, intraoperative cerebrospinal fluid (CSF) leak was significantly associated with infection, whereas longer duration of surgery and unilateral site were associated with resorption. Cranioplasty using frozen autologous bone is associated with a high rate of infective complications. Intraoperative CSF leak is a potentially modifiable risk factor. Meticulous dissection during cranioplasty surgery to minimize the chance of breaching the dural or pseudodural plane may reduce the chance of bone flap.